Nutritional Composition of Feedstuffs for Beef Cattle - Kuhl, Gerry; Simms, Danny; Bandyk, Cathy (My University, 1993)
These typical nutritional values are based on 1982-84 National Research Council publications and recent beef cattle research reports, and will most accurately represent animal utilization when the feedstuffs are used in roughage-based rations for beef cows and growing cattle.
L884_1993-04
Keywords: L884; Livestock; L